Resistance to antibacterial therapy in pediatric febrile urinary tract infections—a single-center analysis - Raupach, Thomas; Held, Jürgen; Prokosch, Hans-Ulrich; Rascher, Wolfgang; Zierk, Jakob (Journal of Pediatric Urology, 2019)
Background: Febrile urinary tract infections (UTIs) are common serious bacterial infections in childhood and require early diagnosis and antibacterial therapy. However, considerable uncertainty exists regarding the optimal antibacterial agent for primary treatment of pediatric UTIs. Additionally, patterns of susceptibility and resistance change over time and microbiological in vitro resistance is not necessarily associated with treatment failure. Here, we analyzed uropathogens, their resistance patterns, and response to antibacterial treatment in children with acute pyelonephritis. Methods: We used billing codes (international classification of diseases) to identify all inpatients aged 0–18 years with febrile UTIs in a German university tertiary care center from 2009 until 2018. Microbial results were retrieved from the laboratory information system for all children, and treatment regimen and treatment response were analyzed in a subgroup of children. Results: We identified 907 children with acute pyelonephritis; in 590 cases (65%) an uropathogen was detected. Escherichia coli (60.8%), Enterococcus faecalis (13.2%), Klebsiella pneumoniae (7.0%), Proteus spp. (5.2%), and Pseudomonas aeruginosa (4.2%) were the most common pathogens. 353 of 436 E. coli isolates (81.0%) were susceptible or intermediate to aminopenicillin/β-lactamase-inhibitor (BLI) combinations. We examined 52 cases where E. coli was resistant to initial therapy with aminopenicillin/BLI combinations: Therapy was changed in 35 cases (67%) and left unchanged in 17 cases (33%), and we found no significant differences in C-reactive protein and leucocyte count in blood and urine between both groups after 3 days. Conclusions: We present the spectrum of uropathogens and susceptibility test results in pediatric UTIs in a tertiary care center. Our findings suggest a satisfactory response to first-line therapy with aminopenicillin/BLI combinations.
CRIS-Team Scopus Importer:2019-12-03
Keywords: Antibiotic susceptibility/resistance; Escherichia coli; Febrile urinary tract infections; Pediatrics